Adaptation of technique for rearing of the coffee berry borer [Hypothenemus hampei (Ferrari)] - Celestino, Flávio Neves; Pratissoli, Dirceu; Machado, Lorena Contarini; Santos Junior, Hugo José Gonçalves dos; Mardgan, Leonardo; Ribeiro, Laura Vaillant (Coffee Science - ISSN 1984-3909, 2016)
The objective of this study was to evaluate rearing techniques of the coffee berry borer, using different natural food sources, forms of asepsis and the storage. The number of offspring produced was evaluated using arabica coffee in beans, arabica coffee in parchment and robusta coffee in beans. For the asepsis of these coffees was used a commercial product based on P2O5 (PCB-P2O5, 30 mL/20 L water), Sodium Hypochlorite (NaClO 5% v v-1) and distilled water (control), these separated in two batches after the asepsis process, one used immediately and the other stored at -20 ºC for 60 days for further use. Among the types of used coffee as a food source in the control (without asepsis), the robusta coffee in beans was the best for the rearing of the coffee berry borer and produced 464.2 insects. For the arabica coffee in beans and in parchment, using asepsis with NaClO and PCB-P2O5, respectively, these did not affect the development of the coffee berry borer and increased the number of individuals produced. When used for the rearing of the coffee berry borer, robusta coffee in beans and performed the asepsis with PCB-P2O5, was produced 535.6 insects. The coffee storage in freezer at -20 ºC for 60 days can in some cases reduce the number of offsprings of the coffee berry borer, but it is important for insect maintenance during the off-season. The best technique for rearing of the coffee berry borer is in robust coffee in beans, using the asepsis with PCB-P2O5, beyond this coffee is less costly.